INVESTIGATING THE IMPLEMENTATION OF COLLABORATIVE STRATEGY READING TO STUDENTS READING NARRATIVE TEXT - Ruswandi, Riki; Ayundhari, Vidia Lantari; Mudrikah, Raifkah Ramilah (Balai Diklat Keagamaan Bandung, 2023)
The aims of the research are to find out the implementation of Collaborative Strategy Reading (CSR) in studentsâ€™ reading narrative text and to describe the studentsâ€™ experience after learning about reading using collaborative strategy reading (CSR) in studentsâ€™ reading narrative text. This research used a qualitative approach with a case study design. The participants of the research were the teacher and the tenth-grade students of SMK Al-Bantari Cianjur with 25 students involved in this research consisting of 14 males and 11 females. The qualitative data was obtained through observation, field notes, interviews, and studentsâ€™ diaries.Â Based on the result of the data analysis, it can be concluded thatÂ Collaborative Strategy Reading (CSR) is able to improve students' reading comprehension of narrative text in the tenth grade of SMK Al-Bantari through four comprehension strategies which include preview, click, and clunk, get-gist, and wrap up by working cooperatively. Collaborative strategy reading also has positive outcomes concerning social relationships and interactions in the classroom. The students gave a positive attitude and actively participated during the implementation of collaborative strategy reading on narrative text. Moreover, collaborative strategy reading increased the students' self-confidence in group discussions, so they bravely expressed their ideas and learned to appreciate the ideas of others. Keywords: Teaching Reading; Narrative text; Collaborative Strategy Reading